2021
DOI: 10.3389/fmats.2020.601059
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of MgB2 Powders as Novel Tools to Fight Fungal Biodeterioration of Heritage Buildings and Objects

Abstract: The 17th–19th century wooden and stone churches are an iconic symbol for the Romanian national heritage, raising urgent needs for the development of efficient and ecofriendly restoration and preservation solutions. Nanotechnology has a great but largely unexplored potential in this field, providing new tools and methods to achieve higher consolidation and protection efficiency, mainly due to the ability of nanoparticles to inhibit the growth and metabolic activity of different biodeteriorating agents, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…After the incubation period (5–7 days at room temperature/24 h at 37 °C), the minimum inhibitory concentration (MIC) values were established as corresponding to the lowest concentration at which the tested plant extract inhibited the growth of the microbial cultures. The final results were calculated and expressed after the solvent inhibitory effect was eliminated [ 92 ].…”
Section: Methodsmentioning
confidence: 99%
“…After the incubation period (5–7 days at room temperature/24 h at 37 °C), the minimum inhibitory concentration (MIC) values were established as corresponding to the lowest concentration at which the tested plant extract inhibited the growth of the microbial cultures. The final results were calculated and expressed after the solvent inhibitory effect was eliminated [ 92 ].…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry has been successfully used over the years in several fields of research, for the analysis of environmental, pharmaceutical, medical and food samples [17,18,27,28,[19][20][21][22][23][24][25][26]. In the context of CH, however, its application is still limited, although some studies have used flow cytometry as a complement to other analytical tools, either in the study of the microorganisms involved in the biodeterioration processes of artworks or the evaluation of the efficiency of potential biocide treatments [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, there is an increased necessity to develop effective and ecofriendly prevention and conservation solutions to protect the material cultural heritage against microbial (re)colonization, with low toxicity risk for human, animal, and environmental health [ 11 , 12 ]. Our research group revealed the efficiency of MgB 2 ecofriendly powders against biodeteriogenic fungi isolated from wooden and stone churches and heritage objects from Romanian counties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%